Tag-araw ng mga ibong hilaga summer of the north birds - Evasco, Eugene Y. (Chikiting Books, 2011)
"Children are not often considered when issues that affect them like the environment and ecology are discussed. But, this wonderful story by the author shows,that it can make a difference in changing adult mindsets and transforming their own areas into sustainable environments. This story is a call to action and a great introduction to the Candaba swamps and the many different migratory birds that visit yearly; that we have re-named and called our very own." Carla M. Pacis.